2019
DOI: 10.7717/peerj.6729
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a tyrosine decarboxylase involved in the biosynthesis of galanthamine inLycoris aurea

Abstract: Background Galanthamine, one kind of Amaryllidaceae alkaloid extracted from the Lycoris species, is used in the treatment of Alzheimer’s disease. In regards to medical and economic importance, the biosynthesis and regulatory mechanism of the secondary metabolites in Lycoris remain uninvestigated. Methods BLAST was used to identify the sequence of tyrosine decarboxylase in the transcriptome of Lycoris aurea (L’Hér) Herb. The enzyme activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
(75 reference statements)
0
20
0
5
Order By: Relevance
“…The enzyme responsible for tyramine biosynthesis is the tyrosine decarboxylase (TYDC) ( Figure 2). Two gene transcript variants of TYDC, named TYDC1 and TYDC2, were identified from the transcriptome of different Amaryllidaceae species including N. pseudonarcissus [41], Narcissus papyraceus [42], Lycoris radiata [43], and L. aureus [44].…”
Section: Biosynthesis Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…The enzyme responsible for tyramine biosynthesis is the tyrosine decarboxylase (TYDC) ( Figure 2). Two gene transcript variants of TYDC, named TYDC1 and TYDC2, were identified from the transcriptome of different Amaryllidaceae species including N. pseudonarcissus [41], Narcissus papyraceus [42], Lycoris radiata [43], and L. aureus [44].…”
Section: Biosynthesis Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…Herb, is an ornamentally and medicinally important perennial herbaceous plant, belonging to the Amaryllidaceae family, from which there were a variety of Amaryllidaceae alkaloids found to exhibit medicinal values [22]. Previous studies of L. aurea have mainly focused on karyotype [23][24][25], physiological analysis [26,27], chemical composition [28][29][30], medicinal usage [31,32], and molecular aspects for gene cloning [33][34][35][36]. For example, several enzymes involved in Amaryllidaceae alkaloids biosynthesis, including cinnamate 4-hydroxylase [34], tyrosine decarboxylase [35] and norbelladine 4'-O-methyltransferase [36] have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of L. aurea have mainly focused on karyotype [23][24][25], physiological analysis [26,27], chemical composition [28][29][30], medicinal usage [31,32], and molecular aspects for gene cloning [33][34][35][36]. For example, several enzymes involved in Amaryllidaceae alkaloids biosynthesis, including cinnamate 4-hydroxylase [34], tyrosine decarboxylase [35] and norbelladine 4'-O-methyltransferase [36] have been identified. Besides, although the induction effects of exogenous methyl jasmonate (MeJA) treatments on Amaryllidaceae alkaloids accumulation has been reported [37,38], little is known about the possible transcriptional or post-transcriptional regulation mechanism of this biological process in L. aurea.…”
Section: Introductionmentioning
confidence: 99%
“…TYDC is an important enzyme, which catalyzes the production of tyramine from L-tyrosine [ 68 ]. It has been found that two transcript variants of TYDC are present in Amaryllidaceae alkaloid producing plants [ 59 , 65 , 66 , 69 , 70 ]. The phylogenetic analysis showed that Amaryllidaceae TYDCs can be divided into two main clusters: “TYDC1” and “TYDC2” [ 59 ].…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…Recently, TYDC1 from Lycoris aurea (L’Hér) Herb. was cloned in Escherichia coli BL21 (DE3) and the expressed enzyme was characterized [ 69 ]. The specialized enzymes involved in stage three of Amaryllidaceae alkaloid biosynthesis are norbelladine synthase (NBS), noroxomaritidine reductase (NR) and norbelladine 4′- O -methyltransferase (N4OMT) ( Figure 2 ).…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%